Find the solution set of non-negative integers ( n , i ) that solves the equation 6 n + 4 = 2 i .
Calculate the sum of the first 6 values of n .
This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try
refreshing the page, (b) enabling javascript if it is disabled on your browser and,
finally, (c)
loading the
non-javascript version of this page
. We're sorry about the hassle.
One of my favorite problems
Rewrite the equation as 3 n = 2 i − 1 − 2 .
We see that 2 i − 1 ≡ 2 ( m o d 3 ) .
From this, multiplying both sides by two gives 2 i ≡ 4 ≡ 1 ( m o d 3 ) . By Fermat's little theorem, i = 2 k .
Hence, the sum of values are k = 1 ∑ 6 6 2 2 k − 4 = 9 0 6 .
6n+4= 2 ^ i
put
n=0 we get 4=2^i => i =2
n=2 6(2)+4= 2^i => 16= 2^i = > i=4
n=10 6(10)+4= 2^i =>64=2^i => i =6
by putting values of n we have arithmetic seq. of range 2, 4 , 6 with common difference d=2
so next values of n can be fouund by puuting values of i.
if i=8 then 6n+4= 256 => n= 42
similarly
i= 10 6n+4= 1024 => n=170
i=12 6n+4 = 4096 => n= 682
now 0+2+10+42+170+682= 906
Problem Loading...
Note Loading...
Set Loading...
We can write the equation 6 n + 4 = 2 i as 6 n = 2 i − 4 ⟹ 3 n = 2 i − 1 − 2 . We can see that as 2 i − 1 − 2 is even, then 3 n is even; so let say n = 2 n 1 ⟹ 6 n 1 + 2 = 2 i − 1 which is 3 n 1 + 1 = 2 i − 2 .
Now, the last equation says 2 i − 2 ≡ 1 ( m o d 3 ) , this can be written as ( − 1 ) ( − 1 ) . . . ( − 1 ) ≡ 1 ( m o d 3 ) with − 1 written i − 2 times (because 2 ≡ − 1 ( m o d 3 ) ). So, we can see that i − 2 must be even.
With, this we suppose the first solutions are i − 2 = 2 , 4 , 6 , 8 , 1 0 , but the solutions for non-negative n are i − 2 = 4 , 6 , 8 , 1 0 , 1 2 ⟹ i = 2 , 4 , 6 , 8 , 1 0
So, when we replacethe values of i in the first equation; we know that the first 6 n solutions are:
n = 0 , 2 , 1 0 , 4 2 , 1 7 0 , 6 8 2 . Their sum is 9 0 6 .